PKM PELATIHAN PROSES PEMBUATAN MANGGO STICKY RICE UNTUK USAHA MIKRO DI KELURAHAN BONA LUMBAN - Riwayani; Safriadi Pohan, Safriadi; Dina Indah Permatasari , Dina Indah; Rifka Hadia Lubis , Rifka Hadia; Anna Basriyani, Anna (Jurnal Masyarakat Indonesia (Jumas), 2025)
The aim of this Community Service Program (PKM) is to enhance the skills of the people of Bona Lumban Village in creating opportunities for micro-enterprises based on local culinary products. Mango Sticky Rice, a popular dessert in Thailand, has great potential to be developed into an innovative and attractive business product. The methods used include hands-on demonstrations, mentoring, and production evaluation. Micro, Small, and Medium Enterprises (UMKM) in Bona Lumban Village, Central Tapanuli Regency, have been engaged as partners in this community service program, which aims to enrich their knowledge of production, packaging, and effective marketing. The results of this activity indicate an improvement in the participants' skills in preparing mango sticky rice and a better understanding of basic entrepreneurship. It is hoped that this program will encourage the people of Bona Lumban Village to develop micro-enterprises, increase family income, and introduce a variety of culinary products that can attract market interest.